Prehospital delay and associated factors among stroke patients in Africa: A systematic review and meta-analysis. - Duguma Debela Ganeti; Amanuel Oljira Dulo; Birhanu Wogane Ilala; Nuritu Bacha Benti; Misganu Diriba; Sadik Abdulwehab; Diriba Etana Tola; Lencho Kajela Solbana (PLoS ONE)
Introduction Stroke is one of the leading causes of death and disability, predominantly affecting low- and middle-income countries. Timely intervention following stroke onset is critical for reducing stroke-related outcomes. However, delayed hospital arrival frequently compromises the effectiveness of treatment. Previous African studies on delayed hospital arrival among stroke patients have reported inconsistent prevalence rates and determinants. Therefore, this systematic review and meta-analysis aimed to assess the overall prevalence of prehospital delay and identify its contributing factors among stroke patients in African countries. Methodology This systematic review and meta-analysis followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. The study protocol was registered with PROSPERO under record number CRD42024545741. Relevant studies were retrieved by searching databases such as PubMed, Google Scholar, the Cochrane Library, AJOL, and Hinari. Additional studies were identified through manual searches and the review of article references. The identified studies were critically evaluated for quality. Data were extracted and exported to R (version 4.2.3) and STATA (version 15.0) for analysis. The pooled prevalence of prehospital delay and the pooled odds ratios for associated factors were subsequently estimated. The risk of bias was assessed using a funnel plot and Egger's test. The results were presented using tables, figures, and statements. Results This systematic review and meta-analysis included 16 studies. The pooled prevalence of prehospital delay among stroke patients was 80% (95% CI: 74-86%). Lack of stroke symptom awareness (AOR = 4.43, 95% CI: 1.04-7.83) and increased distance from a health facility (AOR = 1.28, 95% CI: 1.22-1.34) were significantly associated with prehospital delay. Conclusion and recommendation The prevalence of prehospital delay among stroke patients in Africa is alarmingly high, with contributing factors including a lack of stroke symptom awareness and increased distance from health facilities. Accordingly, stakeholders should implement targeted interventions that enhance community education on stroke warning signs and alleviate geographic barriers to timely care.